Educational inequality in Malaysia (1970-2003) - Rosni, Bakar; Hamri, Tuah (Universiti Malaysia Sarawak, 2005)
1st Meeting of the Society for the Study of Economic Inequality, 20-21 Julai 2005, Univerisitat de Les Illes baleares, palma de Mallorca, Sepanyol